The role of executive function abilities in interleaved vs. blocked learning of science concepts - Park, Jimin; Varma, Keisha; Varma, Sashank (Frontiers in Psychology, 2023)
This study investigated the relative efficacy of interleaved versus blocked instruction and the role of executive function in governing learning from these instructional sequences. Eighth grade students learned about three rock concepts (igneous, sedimentary, metamorphic) and their attributes (origin, texture, composition). Consistent with prior studies and as predicted by current theoretical accounts, students who received interleaved instruction showed better memory (i.e., accuracy on true-false questions) when tested two weeks later, whereas those who received blocked instruction showed better memory when tested on the same day as instruction. Also consistent with prior studies and theoretical accounts, the blocked group showed greater transfer when tested after a retention interval, although this advantage was not significant. Critically, and as predicted, the shifting and inhibition executive function abilities were more predictive of learning from interleaved vs. blocked instruction. These findings lay the groundwork for future studies investigating the role of executive function in learning from different forms of instruction.